WASIAT WAJIBAH DAN IMPLEMENTASINYA TERHADAP HUKUM KELUARGA DI INDONESIA - Syahrul Mubarak (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2020)
Wasiat wajibah is a study in family law in Indonesia that provides opportunities for the adopted children and adoptive parents to inherit. This is stated in Kompilasi Hukum Islam (KHI) in Article 209. Although Indonesia has only recently carried out a family law reforms regarding Wasiat Wajibah compared to other Muslim countries, reform of family law in Indonesia cannot be separated from the meaning and nuances of Islamic law. This article reviews the concept of Wasiat Wajibah in Indonesia, then it is implemented with issues that occur around the community to obtain the relevance in accordance with the changing times.